1995
DOI: 10.1107/s0907444994010486
|View full text |Cite
|
Sign up to set email alerts
|

A new crystal form of bovine heart ubiquinol: cytochromecoxidoreductase: determination of space group and unit-cell parameters

Abstract: Ubiquinol:cytochrome c oxidoreductase, the middle segment of the mitochondrial respiratory chain, is a multi-subunit transmembrane redox enzyme. The purified protein from beef heart mitochondria has been crystallized by three groups in three different forms, but progress toward a structure has been hampered by the limited order (resolution) of the crystals. It has been found that under certain conditions the enzyme crystallizes in a new form suitable for X-ray diffraction studies. These crystals belong to spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…BC1 was crystallized for the first time by two groups (Yue et al, 1991;Kubota et al, 1991) using PEG4000 as a main crystallization agent. Then crystal quality was improved, but still PEG4000 was mainly used (Kawamoto et al, 1994;Berry et al 1995;Lee et al, 1995). The molecular weight of 4000 that was empirically chosen was reasonable for BC1 as discussed above.…”
Section: Crystallization and Metastable Liquid-liquid Phase Separationmentioning
confidence: 99%
“…BC1 was crystallized for the first time by two groups (Yue et al, 1991;Kubota et al, 1991) using PEG4000 as a main crystallization agent. Then crystal quality was improved, but still PEG4000 was mainly used (Kawamoto et al, 1994;Berry et al 1995;Lee et al, 1995). The molecular weight of 4000 that was empirically chosen was reasonable for BC1 as discussed above.…”
Section: Crystallization and Metastable Liquid-liquid Phase Separationmentioning
confidence: 99%
“…These studies revealed that the bovine bc 1 is dimeric with its molecular mass unevenly distributed about the two sides of the membrane. Crystallizations of mitochondrial bc 1 were reported as early as 1991 (Yue et al 1991) and extensive efforts were made by a number of research groups around the world (Berry et al 1992;Yu and Yu 1993;Berry et al 1995;Yu et al 1996;Lee et al 1995), contributing to the final structural solutions of this important complex in various crystal forms. The first bc 1 structure was published nearly ten years ago (Xia et al 1997) for the bovine complex (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Two new crystal forms were reported in 1995 (90). The initial needle crystals were improved in size and shape to give uniform or tapered hexagonal rods.…”
Section: Various Crystal Forms Including Orthorhombic Chicken Bc 1 Crmentioning
confidence: 99%
“…They belonged to the space group P6 1 22 or P6 5 22. They diffracted to 4.6Å using synchrotron radiation recorded on X-ray film, and 3.8Å with imaging plate detector (90).…”
Section: Various Crystal Forms Including Orthorhombic Chicken Bc 1 Crmentioning
confidence: 99%